On Set of All Maximum Independent Sets of Bipartite Graph - V. G. Minasyan (ՀՀ ԳԱԱ հրատ.)
It is shown that the set of all maximum independent sets of bipartite graph is a distributive lattice, which allows to view the problem of generating the maximum independent sets of bipartite graph in a new aspect, namely, to find not all, but only the join-irreducible maximum independent sets. Also an algorithm providing these sets is presented, the complexity of which doesn’t exceed the complexity of the best algorithm providing just one maximum independent set. Ցույց է տրվում, որ երկկողմանի գրաֆի մաքսիմալ անկախ բազմությունների բազմությունը բաշխական կավար է, ինչը թույլ է տալիս երկկողմանի գրաֆի մաքսիմալ անկախ բազմությունների գեներացման խնդիրը դիտել որոշակիորեն նոր 47 ասպեկտում, այն է՝ գտնել ոչ թե բոլոր, այլ միայն միավորմամբ անբաղադրելի մաքսիմալ անկախ բազմությունները։ Նաև ներկայացվում է այդ բազմությունները տրամադրող ալգորիթմ, որի բարդությունը ավելին չէ, քան միայն մեկ մաքսիմալ անկախ բազմություն տրամադրող լավագույն ալգորիթմի բարդությունը։ Показано, что множество всех максимальных независимых множеств двудольного графа есть дистрибутивная решетка, что позволяет рассматривать задачу генерации максимальных независимых множеств двудольного графа в некотором новом аспекте, а именно, найти не все, а только неразложимые в объединение максимальные независимые множества. Также приведен алгоритм, предоставляющий эти множества, сложность которого не больше сложности наилучшего алгоритма, предоставляющего только одно максимальное независимое множество.
Keywords: Mathematics; Science